Effects of Work-Life Balance, Work Experience, Employees Involvement in Sports, and Employees Attitude towards Sports on Employees Job Performance: Mediating Role of Work Involvement - Muhammad Awais Bhatti; Mohammad Alnehabi, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
On a global scale, various industries encounter the challenge of providing goods and services of superior quality, thereby requiring a proficient workforce that demonstrates exceptional Job performance. The equilibrium between professional and personal commitments, employment background, and engagement in athletic activities are all significant factors that influence the efficiency of employees. Hence, the objective of this research is to examine the relationship between work-life balance, sports participation, work experience, work engagement, and the Job performance and productivity of employees in Saudi Arabia. In this quantitative study, the researcher employed a non-probability purposive sampling method to select participants. The data was collected through an online platform. Subsequently, the researcher employed the statistical software SPSS to analyse the data gathered from the participants. Research findings indicate that there is a correlation between employees' improved work-life balance, increased work experience, and active participation in sports activities, leading to a positive influence on their work engagement and ultimately enhancing their Job performance. Nevertheless, it is important to consider that participants in the study may have exhibited response biases such as acquiescence bias, which refers to the tendency to agree with statements, and leniency bias, which refers to the inclination to evaluate everything in a positive or negative manner. These biases have the potential to impact the accuracy of the data collected.